A waitlist randomised control trial of the unified protocol for the treatment of emotional disorders in children and adolescents with chronic medical conditions (The UP-CAM Study): protocol paper - Edith Botchway-Commey; Claire Burton DPsych; Carmen Pace; Jill Ehrenreich-May; Sarah Michelle Kennedy; James Williams; Zeffie Poulakis DPsychClin; Alice Morgan DPsychClin; Vicki Anderson; Louise Crowe (BMC Psychology)
Abstract Background Children and young people with chronic medical conditions (CMCs) are at a greater risk of experiencing emotional disorders (e.g., anxiety and depression) compared to their healthy peers. Transdiagnostic interventions show promise to effectively treat these symptoms, but evidence supporting their use in children and young people with CMC populations is limited. This study aims to adapt and pilot the feasibility, acceptability, and appropriateness of the Unified Protocol for the Treatment of Emotional Disorders in Children and Adolescents (UP-C/A), a transdiagnostic intervention, in children and young people with CMCs. Further, it aims to assess the efficacy of the UP/CA in a randomised control trial (RCT) and examine the influence of this treatment on functional outcomes. Methods The UP-C/A will be adapted using feedback from people with lived/living experience of CMCs (e.g., parents and adolescents), clinicians, and medical professionals working with this population. Participants are children and young people (8 years– 17 years, 11 months old) with a CMC and co-occurring anxiety and/or depressive symptoms. An internal pilot design will be implemented, with the first six participants of the RCT serving as the pilot sample (3 for each group). The RCT participants will be randomised to either a treatment group (n = 30) or waitlist control group (n = 30) and will receive the UP-C/A immediately and eight weeks after enrolment, respectively. Participants will receive 8 to 21 sessions of the intervention, delivered weekly to fortnightly by a trained psychologist. Parent and child-reported measures will be collected at four timepoints: baseline, 8 weeks, immediately post-intervention, and at 3 months post-intervention. Discussion No RCT has evaluated the efficacy of the UP-C/A in children and young people with CMCs. We anticipate that the UP-C/A will be effective at treating anxiety and depression symptoms in children with CMCs, and that short-term gains will be maintained at 3 months post-intervention and be associated with better functional outcomes (e.g., adaptive behaviour and self-regulation). If found to be efficacious, the UP-C/A could be adopted for broad use in public health settings and beyond to help treat emotional disorders in children and adolescents with CMCs. Trial registration Australian and New Zealand Clinical Trials Registry: 12,624,000,114,549; Date: February 23, 2024. WHO Universal Trial Number: U1111-1285-0860.